The Truncated Peptide AtPEP1(9-23) Has the Same Function as AtPEP1(1-23) in Inhibiting Primary Root Growth and Triggering of ROS Burst - Junmei Cui; Ermei Sa; Jiaping Wei; Yan Fang; Guoqiang Zheng; Ying Wang; Xiaoxia Wang; Yongjie Gong; Zefeng Wu; Panfeng Yao; Zigang Liu (MDPI AG, 2024)
Currently, the widely used active form of plant elicitor peptide 1 (PEP1) from Arabidopsis thaliana is composed of 23 amino acids, hereafter AtPEP1(1-23), serving as an immune elicitor. The relatively less conserved N-terminal region in AtPEP family indicates that the amino acids in this region may be unrelated to the function and activity of AtPEP peptides. Consequently, we conducted an investigation to determine the necessity of the nonconserved amino acids in AtPEP1(1-23) peptide for its functional properties. By assessing the primary root growth and the burst of reactive oxygen species (ROS), we discovered that the first eight N-terminal amino acids of AtPEP1(1-23) are not crucial for its functionality, whereas the conserved C-terminal aspartic acid plays a significant role in its functionality. In this study, we identified a truncated peptide, AtPEP1(9-23), which exhibits comparable activity to AtPEP1(1-23) in inhibiting primary root growth and inducing ROS burst. Additionally, the truncated peptide AtPEP1(13-23) shows similar ability to induce ROS burst as AtPEP1(1-23), but its inhibitory effect on primary roots is significantly reduced. These findings are significant as they provide a novel approach to explore and understand the functionality of the AtPEP1(1-23) peptide. Moreover, exogenous application of AtPEP1(13-23) may enhance plant resistance to pathogens without affecting their growth and development. Therefore, AtPEP1(13-23) holds promise for development as a potentially applicable biopesticides.